2009
DOI: 10.1124/mol.109.058545
|View full text |Cite
|
Sign up to set email alerts
|

KU135, a Novel Novobiocin-Derived C-Terminal Inhibitor of the 90-kDa Heat Shock Protein, Exerts Potent Antiproliferative Effects in Human Leukemic Cells

Abstract: The 90-kDa heat shock protein (Hsp90) assists in the proper folding of numerous mutated or overexpressed signal transduction proteins that are involved in cancer. Consequently, there is considerable interest in developing chemotherapeutic drugs that specifically disrupt the function of Hsp90. Here, we investigated the extent to which a novel novobiocin-derived C-terminal Hsp90 inhibitor, designated KU135, induced antiproliferative effects in Jurkat T-lymphocytes. The results indicated that KU135 bound directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 41 publications
7
74
1
Order By: Relevance
“…PARP may be cleaved by numerous caspase-1-like caspases in vitro and is one of the primary cleavage targets of caspase-3 in vivo. Furthermore, ROS may activate caspase-3, which results in the cleavage of PARP into an 89-kDa fragment (6,(15)(16)(17)20). In the present study, a Hoechst 33258 staining assay indicated that treatment with 200 µM H 2 O 2 alone induced notable cell apoptosis in PC12 cells, while 80 µM PF produced a reduction in the extent of apoptosis-associated nuclear fragmentation (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…PARP may be cleaved by numerous caspase-1-like caspases in vitro and is one of the primary cleavage targets of caspase-3 in vivo. Furthermore, ROS may activate caspase-3, which results in the cleavage of PARP into an 89-kDa fragment (6,(15)(16)(17)20). In the present study, a Hoechst 33258 staining assay indicated that treatment with 200 µM H 2 O 2 alone induced notable cell apoptosis in PC12 cells, while 80 µM PF produced a reduction in the extent of apoptosis-associated nuclear fragmentation (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The novobiocin analogue, KU-135, was synthesized as described previously, and purity was verified as Ͼ95% by NMR and mass spectrometry (14). Recombinant human soluble TRAIL was a kind gift from Dr. Thomas Sayers (National Institutes of Health).…”
Section: Chemicals Reagents and Plasmidsmentioning
confidence: 99%
“…Compared with N-terminal inhibitors, the antibiotic novobiocin (NB) binds the C terminus of Hsp90 and, through Hsp90 C-terminal inhibitions, induces client protein degradation without induction of the prosurvival HSR (Burlison et al, 2008;Shelton et al, 2009;Matthews et al, 2010;Eskew et al, 2011). We have previously reported the synthesis and evaluation of NB analogs that exhibit improved potency over NB (Shelton et al, 2009;Matthews et al, 2010;Eskew et al, 2011;Kusuma et al, 2014). In this article, we report a new C-terminal inhibitor, KU675, that exhibits potent antiproliferative effects in prostate cancer cells and a preference for the inhibition of Hsp90a.…”
Section: Introductionmentioning
confidence: 99%